Kajian Rute Angkutan Umum di Banyumanik Semarang Terkait Transportasi yang Berkelanjutan - Rithoma, Ricky; Rakhmatulloh, Anita Ratnasari (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
Uncontrolled and sprawling urban growth may cause inefficiencies in the city’s provision of public facilities and infrastructures including for transportation, which may then contribute to the failure in the provision of public transport for the community. People are then subjected to provide their own mode of transport in the form of private vehicles. Those who can not, whether due to economic or social factors, are captive to use public transport which is inefficient in terms of cost, time and other service characteristics. As a result, transportation sustainability is difficult to achieve, whether economically (with growing investment and lo cost transportation for the masses), socially (with the guarantee for security and safety for the masses), or ecologically (with low pollution from fuel burning). There is a dire need for a public transport system which can reach the population, one of which in terms of service routes.